Transparansi Keuangan Dalam Partai Politik - Muhtar Said (Indonesian State Law Review, 2020)
The aim of the article is to analyze financial transparency of the political parties. The methods used normative Juridical. Political parties are an important element of the state system in a country that adheres to the principle of democracy. Political parties can be a place for people to channel their aspirations, but increasingly. Therefore, as an important element in order democracy, political parties must begin to improve more transparent to the public about the management and use of party funds. Law No. 14 of 2008 has provided a standard for political parties wishing to uphold the agreement by making an Information Management and Documentation Officer (PPID).